Focauldian Productive Power from a Discursive View(Case Study: Foreign Policy of the Islamic Republic of Iran) - Mohammadreza Tajik; Khosrow Rezazadeh (رهیافتهای سیاسی و بین المللی)
This study is going to analyze the productive power of Foucault from a discursive viewpoint and investigate its role in the foreign policy of the Islamic Republic of Iran. In Foucault’s view, the productivity of power is the form of making establishment. Foucault equals power with act and practice; so, he places power analyses instead of power theory. Once power produces knowledge and discourse, it can be turned to practice. In fact, without establishing truth regime, that is discourse, power cannot be crystalized in practice. Power can become subjugation, domination, normalization or the Hegemone power of life. It makes discourse in order to create subject and object.  Implementing this policy in the postmodern era requires power, knowledge and exercising a Hegemone discourse for establishing a truth regime in the international system. This study is going to answer the question that how Iran’s foreign policy could efficiently use power and discourse in an optimal way to reach its maximal interests? The recognition of the power and knowledge relations in this era, discourse applying the genealogy and archeology elements and the understanding of Michel Foucault of discourse is what this writing is organized around.